A new species of Neotropical Enallagma Charpentier of the cyathigerum complex from Tobago (Odonata: Coenagrionidae) - Donnelly, Thomas W.; Michalski, John (Zootaxa, 2025)
Enallagma tobagoensis sp. nov. (Holotype, male: Tobago, St. John Parish, stream along Northside Road (N 11.2868°, W 60.6808°, 8 August 2019, Thomas W. Donnelly and John Michalski leg.) is described based on two incomplete males. The new species is a smaller melanic version of the Enallagma cyathigerum complex and is the first member of that group known from the Neotropical region.